KETIDAKPASTIAN LINGKUNGAN MEMODERASI HUBUNGAN ANTARA SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL - Simangunsong, Wita Efalina; Irma Rentauli Sitorus; Lisbet Pardede; Ade Karina Marpaung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of management accounting systems on managerial performance and to examine the role of environmental uncertainty as a moderating variable in this relationship. In the face of a dynamic and uncertain business environment, companies are required to have management information systems that can provide relevant and accurate data to support effective decision making. This study uses a quantitative approach with an explanatory research method. Primary data was obtained through the distribution of questionnaires to 85 respondents who hold managerial positions in various companies. The data analysis technique used is moderated regression analysis (MRA). The results of the study indicate that the management accounting system has a positive and significant effect on managerial performance. Additionally, environmental uncertainty was found to significantly moderate the relationship between management accounting systems and managerial performance. These findings emphasize the importance of adaptive management accounting systems in responding to external environmental dynamics to enhance managerial performance in companies.